Introducing a Supportive Framework to Address Students’ Misconceptions and Difficulties in the Learning Mathematical Proof Techniques: A Case of Debark University in Ethiopia - Belay, Aschale Moges; Machaba, France; Makgakga, Tšhegofatšo Phuti (Research in Social Sciences and Technology, 2024)
This research article is about "Introducing a Supportive Framework to Address Students' Misconceptions and Difficulties in Learning Mathematical proof techniques (MPT): A Case of Debark University”. This study aims to develop, introduce, and implement a supportive framework to overcome students’ misconceptions and difficulties in MPT. The framework, named IR2CP2CE, was developed, introduced, and implemented at Debark University in Ethiopia using various data-gathering instruments such as questionnaires, interviews, classroom observations, and document analysis from students and instructors. The study collected data over four months, including the implementation of a supportive framework using mixed, quasi-experimental, and pragmatism research approaches, designs, and paradigms respectively. The internal reliability of the data-gathering instruments was interpreted using Cronbach’s coefficient, Spearman-Brown, Spearman correlations, Kuder-Richardson 20 and 21, and difficulty and discrimination indices. The results showed that the implementation of the supportive framework led to significant improvements in students’ academic performance in MPT, regardless of factors such as gender, academic year category, and preliminary knowledge and proving skills. This study recommends additional imperatives for practice and future research.